Repeated long-term cover cropping and nitrogen fertilization enhance soil multifunctionality - Lin Li; Wanyu He; Qilong Du; Xue Zhao; Minghui Meng; Guangjin Wu; Guangxi Liu; Simeng Wang; Jun Wang; Fazhu Zhao; Jieying Wang (Agriculture, Ecosystems & Environment, 2026)

Rapid screening method of glucocorticoid residues in sample-limited cell-cultured meat - Peiwen Yu; Simeng Li; Chen Zhang; Xiaohui Li; Hongping Wang; Fen Jin (Food Research International, 2026)

Adaptive laboratory evolution of Lactiplantibacillus plantarum for enhanced lactose metabolism: Phenotypic changes and underlying molecular mechanisms - Hong Li; Simeng Wang; Jiao Wu; Xingyu Li; Ruihang Liu; Yuenan Wang; Tong Dan (Food Research International, 2026)

Multi-functional porous nanochitin films for PFAS removal and supercapacitor applications - Lucas J. Andrew; Simeng Li; Evan J. Wong; M. Andrea Ortiz Medrano; Madjid Mohseni; Mark J. MacLachlan (Chemical Engineering Journal, 2026)

A novel conformationally constrained RGD-based cyclic peptide targeting integrin αvβ6 protein for antitumor therapeutic applications - Yang Lv; Chunyu Qu; Yue Lei; Hongrui Zhang; Zeyan Jiang; Simeng Zhao; Tingting Li; Xiaodan Wu; Zhiqiang Wang (Chemico-Biological Interactions, 2026)

Warming attenuates root-induced decomposition enhancement via soil moisture limitation in a subtropical forest of China - Shuai Liu; Simeng Wang; Yuxiang Xu; Xiangliang Li; Qianqian Xi; Chuansheng Wu (Acta Oecologica, 2026)

Possible Causes for the Dipole Pattern of Spring Forest Fires between the Indo-China Peninsula and Northeast Asia - Simeng Li; Haishan Chen; Wenjian Hua; Xiangxu Kong (Advances in Atmospheric Sciences, 2026)

The mixed cover crops and nitrogen fertilization decrease the soil microbial dormancy - Simeng Wang; Xue Zhao; Wanyu He; Jieying Wang; Minghui Meng; Xiya Xiong; Min Xie; Guangjin Wu; Qilong Du; Lin Li; Guangxi Liu; Jun Wang; et al. (Plant and Soil, 2026)

Evolution of mid-late Holocene fire dynamics and its driving mechanisms: Evidence from Balikun Lake, Xinjiang, China - Panpan Cui; Wen Li; Yuqin Zhou; Yingqiu Gao; Simeng Wang (Quaternary International, 2026)

Unpacking rural spatial shrinkage in metropolitan fringe of China: A cross-scale human-land relationship perspective in Chedong, Guangzhou - Simeng Li; Ren Yang; Hualou Long; Wen Yang; Chen Zhang (Journal of Rural Studies, 2026)

Integrated removal of calcium and magnesium and extraction of lithium from the mamicuo salt lake in tibet using a pyrrole fluoride-β-diketone/TRPO synergistic system - Simeng Yang; Dong Shi; Lianmin Ji; Yuze Zhang; Jinfeng Li; Xiaowu Peng; Shaolei Xie; Hailong Lu; Yong Niu; Lejie Xu; Lijuan Li (Journal of Environmental Chemical Engineering, 2026)

Projection of distribution shift for Pacific saury (Cololabis saira) in the Northwestern Pacific Ocean under climate change - Zi Yang; Simeng Li; Xiaoxue Liu; Libin Dai; Jie Cao; Siquan Tian (Regional Studies in Marine Science, 2026)

Microplastics enter strawberry fruit tissues directly through the epidermis - Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Lihui An; Fen Jin (Journal of Hazardous Materials, 2026)

Reduction of As(V)-bearing goethite by dissolved organic matter from arsenic-prone groundwater during the repeated electron shuttling - Xiaojun Feng; Zhengqi Su; Simeng Li; Xiaoxing Ming; Di Zhang; Huaming Guo (Journal of Hazardous Materials, 2026)

Metagenomic analysis of lactic acid bacteria communities in inner Mongolian fermented dairy products: influence of milk source and geography - Hong Li; Haimin Hu; Wenhui Lu; Jinhui Liu; Qingting Peng; Simeng Wang; Tong Dan (Food Research International, 2026)

Sex-dependent acute oral toxicity and in vivo distribution of 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA) in rats - Simeng Li; Peiwen Yu; Bowen Li; Xiaohui Li; Hongping Wang; Fen Jin (Food and Chemical Toxicology, 2026)

An efficient embryogenic cell suspension enabling somatic embryogenesis in Phyllostachys edulis - Simeng Kong; Huan Liu; Kaiting Wang; Xiaohong Zhou; Xinyi Yang; Juan Zhuo; Xiangyu Li; Xinchun Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A new strain of Trichoderma shows improved biocontrol of Fusarium root rot in ginseng via functional metabolites, defense induction and rhizosphere regulation - Simeng Zhao; Liwei Wang; Chao Li; Zhangxin Hou; Xinping Yang; Hongyan Yang (Rhizosphere, 2026)

Freeze-thaw cycles intensified the synergistic inhibitory effects of enrofloxacin and UV-328 on rye seedling growth - Ning Li; Guozhang Bao; Simeng Chen; Yanan Xu; Yue Yuan; Zimin Fu (Journal of Environmental Management, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Long-term scenarios for climate adaptation of cotton crops in China, considering multidimensional biophysical and socio-economic scenario analysis - Simeng Guo; Fengqi Wu; Yuhan Wang; Jian Wang; Zhenggui Zhang; Zhanlei Pan; Chenxi Chong; Pengcheng Li; Weibin Huang; Guilan Sun; Xin Li; Shuchen Wang; et al. (Journal of Cleaner Production, 2026)

A gas–liquid entrainment scrubber for fine silica dust control in an ore-crushing workshop: Industrial field testing and integrated assessment - Tao Wei; Ruhua Zhu; Bao Zhang; Linling Zhu; Simeng Fan; Huiqing Luo; Zhaoxing Li; Bulong Bu; Zhentao Li; Xiaochuan Li; Fei Gao (Journal of Cleaner Production, 2026)

The magnetic characteristics of surface soils in Nanchang City, China, and their responses to heavy metal contamination - Gao Yingqiu; Li Wen; Wang Simeng; Zhou Yuqin; Cui Panpan (Environmental Geochemistry and Health, 2026)

Differential cannabinoid-like effects, receptor affinity and physiologically based pharmacokinetics of the synthetic cannabinoids 4F-MDMB-BINACA, 4F-MDMB-BICA and 5F-MDMB-PICA in mice: A comparative study - Yawen Xu; Simeng Zhang; Xuesong Shi; Lixin Kuai; Yuanyuan Chen; Kaixi Li; Xiangyu Li; Yanling Qiao; Dan Wang; Cheng Jiang; Peng Xu (Toxicology and Applied Pharmacology, 2025)

The sanitation in restrooms to respiratory health: modelling concentration distribution changes of bioaerosols across buildings with/without semi-open settings - Ting Zhang; Zuming Wang; Simeng Zhang; Yuying Chen; Guiying Li; Taicheng An (Environmental Pollution, 2025)

Thermodynamic modeling and absorption capability evaluation of a novel absorbent AMP + HEPZ for CO2 capture - Simeng Li; Zhisheng He; Yongqiang Ren; Jian Chen; Shisen Xu (Chemical Engineering Journal, 2025)

Feasibility of planting shrubs in arid areas from a water balance perspective - Chenguang Zhao; Chao Guan; Tengfei Yu; Jiazheng Wang; Huiying Li; Xia Wang; Baojun Zhang; Simeng Kou; Xuejuan Liu; Changming Zhao (Journal of Hydrology, 2025)

Oral administration of large-leaf yellow tea protein-derived oligopeptides alleviates UV-induced skin photoaging through the inhibition of MAPK/AP-1/MMP9 signaling pathway - Ziyi Shen; Simeng Zhou; Yaru Zhang; Yuan Zhang; Hongyan Wang; Daxiang Li; Yijun Wang; Zhongwen Xie; Huifang Ge (Food Research International, 2025)

Enhanced removal of per- and poly-fluoroalkyl substances (PFAS) by modified clay: Adsorption behavior, simulation, and regeneration - Simeng Li; Madjid Mohseni (Colloids and Surfaces C: Environmental Aspects, 2025)

Biomimetic solar-driven interfacial evaporation system with effective desalination and volatile organic compounds removal performance - Boli Nie; Weiwei Zhang; Yafu Li; Yuhao Li; Yanming Meng; Xi Zhao; Simeng Niu; Yan-Chao Wu; Hui-Jing Li (Chemical Engineering Journal, 2025)

Deep eutectic solvents molecular interfacial engineering for suppressing chemical corrosion in Li metal batteries - Simeng Wang; Hongtao Li; Caiwen Zhao; Pengtao Guo; Minting Luo; Yu Liang; Jiajia Huang; Shimou Chen (Chemical Engineering Journal, 2025)

Therapeutic strategy for corneal edema: Nicotinamide - based anterior chamber perfusion agent for efficacy - verified treatment - Liwei Huang; Xiaomin Liu; Xiaoming Wu; Haoyun Duan; Simeng Zheng; Xiangyue Hu; Shengqian Dou; Xiaoyu Li; Zongyi Li; Qingjun Zhou; Lixin Xie (Chemical Engineering Journal, 2025)

Chitin nanocrystal/carboxymethyl cellulose bilayer emulsion with rigid inner layer and flexible outer shell for ultra-stable encapsulation of fish oil - Yufei Sun; Qianxi Deng; Simeng Ji; Yuewen Li; Kao Wu; Ying Kuang; Fatang Jiang; Pengpeng Deng (Carbohydrate Polymers, 2025)

Naphthenic acids (NAs) - tolerant aerobic granular sludge: Removal performance, degradation mechanism, and microbial response - Jin Li; Shasha Liu; Simeng Li; Jiayu Song; Qinghong Wang; Chunmao Chen (Journal of Environmental Management, 2025)

A transcriptomics-based analysis provides insights into the sex-dependent reproductive toxicity of DEHP in zebrafish (Danio rerio) - Shirui Liu; Simeng Yu; Yankun Huang; Jingyun Zhang; Kai Song; Shenbao Qu; Cixin Li; Aijiang Yang; Xia Hu (Environmental Toxicology and Pharmacology, 2025)

Changes in Physiological Characteristics of Rye Treated with 2,4-Epibrassinolide Under Combined Stress of Cd and Freeze-Thaw - Lingzhi Tian; Guozhang Bao; Huixin Wang; Yanan Xu; Simeng Chen; Yunqi Jiang; Guomei Li (Water, Air, & Soil Pollution, 2025)

Novel quantitative method of reactive losses of ambient VOCs coupling chemical transport model simulation with receptor measurement - Yao Gu; Baoshuang Liu; Simeng Ma; Zhongwei Luo; Jinqiu Zhang; Danni Liang; Yafei Li; Yufen Zhang; Yinchang Feng (Journal of Hazardous Materials, 2025)

Glucose membrane-assist pyrolysis engineered ultrafine FeP/CoP3-doped hollow carbon nanospheres: Enhanced bifunctional oxygen catalysts for rechargeable zinc-air batteries - Fan Li; Jilan Long; Li Kang; Fei Zhao; Simeng Ding (Chemical Engineering Journal, 2025)

Carbon, nitrogen, and phosphorus ecological stoichiometry in Cenchrus fungigraminus and soil under waterlogging stress - Simeng Song; Hengyu Zhou; Pingxuan Li; Lin Zhang; Dewei Su; Dan Zheng; Zhaoxiong Zhang; Zongzhi Luo; Shikui Yu; Bin Liu; Zhanxi Lin; Dongmei Lin (Plant and Soil, 2025)

Nuclear protein 1 protects against neonatal hypoxic-ischemic encephalopathy by inhibiting neuronal ferroptosis by improving iron storage - Xining He; Simeng Wei; Yunsheng Fu; Hongxia Li; Jie Zhang; Li Liu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Ligand exchange by As(V) enhanced desferrioxamine B-induced goethite dissolution: Insights into As mobilization in groundwater systems - Simeng Li; Wei Xiu; Xin Liu; Zhixin Fang; Jonathan R. Lloyd; Huaming Guo (Applied Geochemistry, 2025)

Osthole–pyrethrins combination loaded onto hollow microsphere silica nanoparticles inhibits Fusarium solani growth and controls root rot incidence in Cynanchum auriculatum - Xiaomeng Fei; Bing Xie; Junjie Tang; Lixia Wang; Yong Zheng; Haifeng Kuai; Simeng Li; Daoguo Zhang; Wei Gu (Physiological and Molecular Plant Pathology, 2025)

BDD electrode pulsed alternating electrochemical oxidation of sulfamethazine in antibiotic wastewater: Process optimization and degradation mechanism - Simeng Hu; Yongshang Lv; Xifei Hou; Jiahao Li; Yaxuan Hou; Xiaohua Fu; Tao Xu (Environmental Research, 2025)

Tracing the carbon footprint of cotton garments from seed to garment: Evidence from an empirical study of multiple sites in China - Shuchen Wang; Chenxi Chong; Weibin Huang; Simeng Guo; Yuhan Wang; Yaopeng Zhang; Zhanlei Pan; Jian Wang; Xin Li; Wenqi Zhao; Zhenggui Zhang; Zhanbiao Wang (Resources, Conservation and Recycling, 2025)

Exogenous γ-aminobutyric acid (GABA) effectively alleviates the synergistic inhibitory effect of freeze-thaw and copper combined stress on rye seedling growth - Huixin Wang; Guozhang Bao; Lingzhi Tian; Simeng Chen; Yanan Xu; Guomei Li (Journal of Environmental Management, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dissipation patterns of trisiloxane ethoxylates in cucumber plants and field soils: Insights from different end-capping groups - Simeng Li; Xiaohui Li; Chen Zhang; Bowen Li; Peiwen Yu; Qin Dai; Hongping Wang; Fen Jin (Journal of Hazardous Materials, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

High strength, gas barrier and hydrophobic konjac glucomannan/glutenin films with semi-interpenetrating network for cherry tomato preservation - Pengpeng Deng; Zihao Wang; Yuewen Li; Simeng Ji; Yufei Sun; Qianxi Deng; Juanjuan Chen; Fatang Jiang (Food Hydrocolloids, 2025)

Seasonal variation of underwater sound propagation in the Beibu Gulf - Feihong Zeng; Lingling Xie; Mingming Li; Qiang Li; Simeng Liu (Frontiers in Marine Science, 2025)
Variations in the underwater sound speed significantly influence sound propagation in the ocean, thereby impacting both underwater navigation systems and a substantial portion of marine organisms reliant on sound. This study utilizes cruise data from the Beibu Gulf during the summer and winter of 2023–2024 to explore the seasonal variations in temperature and salinity affecting the sound speed distribution and characteristics of sound propagation. Results indicate significant differences in the sound speed on either side of the 30-m isobath in the Beibu Gulf, with pronounced changes corresponding to seasonal temperature and salinity variations. In summer, the sound speed in the Beibu Gulf exhibits a north-high–south-low pattern. In areas shallower than 30 m, the sonocline is predominantly positive or absent, whereas, in deeper areas, it is mainly negative. During winter, there is a south-high–north-low pattern in sound speed across the Beibu Gulf, with pronounced sound speed extremes in areas shallower than 30 m. Sound propagation simulations based on the Beibu Gulf sound-speed field reveal that sounds at the 100-Hz frequency propagate significantly farther and cover larger areas in depths less than 30 m compared to deeper areas. In summer, this phenomenon is more pronounced than in winter due to the presence of positive sonoclines. The results have significant implications for target detection, underwater acoustic communication, and the protection of aquatic animals that rely on underwater sound for survival in the Beibu Gulf.

Self-Compensating strategy of electronic Structure-Modulated selenide @ carbon nanotube / carbon nanofiber for High-Efficiency electromagnetic wave absorption and corrosion resistance - Simeng Wu; Yanxiang Wang; Jiangyiming Jiang; Yibo Li; Dongming Liu (Chemical Engineering Journal, 2025)

Protein Phosphatase 2ACα Regulates ATR-Mediated Endogenous DNA Damage Response Against Microcephaly - Lin Lin; Jing Ding; Simeng Liu; Chunying Liu; Qing Li; Xiang Gao; Yamei Niu; Wei-Min Tong (Molecular Neurobiology, 2025)

Responses of magnetic properties to heavy metals pollution recorded by sediments of Nanchang City reach of Ganjiang River, East China - Simeng Wang; Wen Li; Changsheng Ye; Yingqiu Gao; Yuqin Zhou (Environmental Geochemistry and Health, 2025)

Distinctive Neural Substrates of low and high Risky Decision Making: Evidence from the Balloon Analog Risk Task - Zhenlan Jin; Simeng Li; Changan Wang; Xiaoqian Chai; Junjun Zhang; Ling Li (Brain Topography, 2025)

Concentration, pathogenic composition, and exposure risks of bioaerosol in large indoor public environments: A comparative study of urban and suburban areas - Jiasheng Ni; Simin Huang; Zhishu Liang; Zhen Chen; Simeng Zhang; Guiying Li; Taicheng An (Science of The Total Environment, 2024)

Lithium extraction from high-Mg brines using N523/esters systems - Lianmin Ji; Dong Shi; Yuze Zhang; Jinfeng Li; Xiaowu Peng; Shaolei Xie; Simeng Yang; Nan Chen; Hailong Lu; Yong Niu; Lijuan Li (Journal of Water Process Engineering, 2024)

Unveiling the critical roles of nascent MnO2 in accelerating permanganate carbocatalysis - Jun Wang; Simeng Bi; Li Wei; Yi Shen; Fanpeng Meng; Yang Zhang; Xiaoyao Tan (Journal of Hazardous Materials, 2024)

Contribution of plastic solid components to volatile organic compounds formation during plastics combustion - Xinglei Wang; Simeng Tang; Ling Ding; Xinran Qiu; Zhenming Zhang; Li Xu; Xujun Liang; Xianfei Huang; Xuetao Guo (Journal of Hazardous Materials, 2024)

Recent advances on transport and transformation mechanism of nanoplastics in lung cells - Simeng Zhang; Hangxi Zhang; Yichen Li; Zhiwei Sun; Yueyue Chen (Science of The Total Environment, 2024)

Climate warming and nitrogen deposition had no significant interaction effect on litter decomposition of subtropical mountain forest in Southwest China - Yue Li; Simeng Wang; Ying Wang; Menglong Bu; Shuai Liu; Chuansheng Wu (Plant and Soil, 2024)

Inhibition of BCAT1 expression improves recurrent miscarriage by regulating cellular dysfunction and inflammation of trophoblasts - Guangli Xu; Chao Tian; Yanru Li; Lei Fang; Jing Wang; Zhuqing Jing; Simeng Li; Ping Chen (Cell and Tissue Research, 2024)

Maternal Supplementation of Collagen Peptide Chelated Trace Elements Enhances Skeletal Muscle Development in Chicks - Jiao Wang; Zhenwu Huang; Simeng Li; Zengpeng Lv (Biological Trace Element Research, 2024)

Natural variation in photosynthetic electron transport of wheat flag leaves in response to dark-induced senescence - Cheng Yang; Zishan Zhang; Yuan Yuan; Deqi Zhang; Haiyang Jin; Ying Li; Simeng Du; Xiangdong Li; Baoting Fang; Fang Wei; Ge Yan (Journal of Photochemistry and Photobiology B: Biology, 2024)

Large-leaf yellow tea protein derived-peptides alleviated dextran sodium sulfate-induced acute colitis and restored intestinal microbiota balance in C57BL/6 J mice - Huifang Ge; Fengxue Qi; Ziyi Shen; Hongyan Wang; Shangliang Zhu; Simeng Zhou; Zhongwen Xie; Daxiang Li (Food Chemistry, 2024)

Risk assessment model for dust explosion in dust removal pipelines using an attention mechanism-based convolutional neural network - Yang Li; Gaozhi Cui; Qinglin Han; Simeng Chen; Shuaishuai Lu (Stochastic Environmental Research and Risk Assessment, 2024)

Thyroglobulin as a Sensitive Biomarker of Iodine Status in Mildly and Moderately Iodine-Deficient Pregnant Women - Yujie Jiang; Simeng Gu; Zhe Mo; Xueqing Li; Chenyang Liu; Yahui Li; Guangming Mao; Yuanyang Wang; Fanjia Guo; Xiaoming Lou; Xiaofeng Wang (Biological Trace Element Research, 2024)
Pregnant women are more susceptible to iodine deficiency. However, there are limitations in existing indicators for the evaluation of iodine nutrition in pregnant women. The study aimed to explore whether thyroglobulin (Tg) can be used as a more sensitive biomarker for pregnant women with mild and moderate iodine deficiency. A repeated-measure study was conducted among 1332 pregnant women in Zhejiang Province, China. Serum and urine specimens were collected at a mean of 10, 17, and 32 weeks of pregnancy, respectively; thyroid-stimulating hormone (TSH), Tg, and urinary iodine concentrations were measured. Linear mixed effects models were used to determine the associations between interaction of iodine concentrations and increasing gestation week and TSH and Tg, where participants were divided by urinary iodine concentration (UIC). The median Tg concentration was 11.56, 11.45, and 12.43 μg/L in the first, second, and third trimesters, respectively. After controlling the covariates, the interaction effects between the iodine status and gestation week were significant for both TSH and Tg ( p = 0.038 and p = 0.007, respectively). TSH increased with the week of gestation in both iodine concentration groups. Tg increased with advancing pregnancy in the iodine-deficient group whereas it did not in the iodine-sufficient group. There was no significant variation in TSH at each trimester, and Tg was higher in the iodine-deficient group than in the iodine-sufficient group. Tg may be a more sensitive iodine status biomarker than TSH for pregnant women with mild-to-moderate iodine insufficiency.

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Dissipation and potential risk of tristyrylphenol ethoxylate homologs in peanuts by spraying and root irrigation: A comparative assessment - Hongping Wang; Minjie Li; Simeng Li; Xueying Chen; Bowen Li; Hua Shao; Fen Jin (Journal of Hazardous Materials, 2024)

The abundance and pathogenicity of microbes in automobile air conditioning filters across the typical cities of China and Europe - Kaifei Su; Zhishu Liang; Simeng Zhang; Wen Liao; Jianwei Gu; Yunlong Guo; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2024)

Zinc oxide nanoparticles damage the prefrontal lobe in mouse: Behavioral impacts and key mechanisms - Dan Zhang; Zhiyuan Wang; Hongmei Deng; Simeng Yi; Tao Li; Xinjiang Kang; Jun Li; Chang Li; Tingting Wang; Bo Xiang; Guang Li (Toxicology Letters, 2024)

Comprehensive sensitivity analysis of the WRF model for meteorological simulations in the Arctic - Tong Zhang; Le Cao; Simeng Li; Chenchao Zhan; Jiandong Wang; Tianliang Zhao (Atmospheric Research, 2024)

Occurrence and distribution of trisiloxane ethoxylates in citrus orchard soils in China: Analytical challenges - Simeng Li; Ning Yue; Minjie Li; Xiaohui Li; Bowen Li; Hongping Wang; Jing Wang; Fen Jin (Science of The Total Environment, 2024)

Imidacloprid triggered changes in strawberry fruits on edible quality and phenolic profiles by applied at two growth stages - Ning Yue; Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Xueying Chen; Fen Jin (Food Research International, 2024)

Quantifying physiological contributions to yield loss in response to planting date in short-season cotton under a cotton wheat double-cropping system - Simeng Guo; Yingchun Han; Guoping Wang; Fengqi Wu; Yaoyu Jia; Jiale Chen; Xiaofei Li; Wenli Du; Yabing Li; Lu Feng (European Journal of Agronomy, 2024)

Effect of light intensity on the accumulation of protostane triterpenes in Asian water plantain (Alisma orientale) - Wenqing Wu; Simeng Li; Wei Gu; Rong Tian; Man Luo; Junjie Tang; Min Tang; Yinzhi Wu (Acta Physiologiae Plantarum, 2024)

Intelligence detection of oil absorption in French fries by surface profiles - Simeng Wang; Shuli Zhao; Nan Wang; Qianru Lu; Haile Zhao; Ying Liu; Jinwei Li; Liuping Fan (Food Research International, 2024)

Zinc Oxide Nanoparticles Induce Renal Injury by Initiating Oxidative Stress, Mitochondrial Damage and Apoptosis in Renal Tubular Epithelial Cells - Shuang Liu; Han Zhou; Yang Shi; Simeng Yi; Xinyu Wang; Jingyan Li; Bin Liao; Jimin Cao; Guang Li (Biological Trace Element Research, 2024)

Hydrogels as water and nutrient reservoirs in agricultural soil: a comprehensive review of classification, performance, and economic advantages - Yudi Wu; Simeng Li; Gang Chen (Environment, Development and Sustainability, 2023)

Rural Development Transformation and Social Governance from the Perspective of Specialization: A Case Study of Ruiling Village in Guangzhou City, China - Yuancheng Lin; Ren Yang; Simeng Li (Chinese Geographical Science, 2023)

5-Methoxytryptophan ameliorates endotoxin-induced acute lung injury in vivo and in vitro by inhibiting NLRP3 inflammasome-mediated pyroptosis through the Nrf2/HO-1 signaling pathway - Yang Ma; Zhixue Wang; Xiaoyang Wu; Zijian Ma; Jia Shi; Simeng He; Shaona Li; Xiangyun Li; Xiangkun Li; Yan Li; Jianbo Yu (Inflammation Research, 2023)

Effects of anthropogenic emissions and meteorological conditions on diurnal variation of formaldehyde (HCHO) in the Yangtze River Delta, China - Yurong Gao; Hao Pan; Le Cao; Chunsong Lu; Qingjian Yang; Xichang Lu; Hongyi Ding; Simeng Li; Tianliang Zhao (Atmospheric Pollution Research, 2023)

Nitrogen stress alters trade-off strategies between reproduction and vegetative growth in soybean - Menglong Bu; Yue Li; Simeng Wang; Changjiang Huang; Chuansheng Wu; Shuai Liu (Brazilian Journal of Botany, 2023)

Blocking of programmed cell death-ligand 1 (PD-L1) expressed on endothelial cells promoted the recruitment of CD8+IFN-γ+ T cells in atherosclerosis - Qi Li; Simeng Wei; Yue Li; Fengjiao Wu; Xiaoling Qin; Zhongsha Li; Jingyu Li; Chang Chen (Inflammation Research, 2023)

Changes in within-boll yield components explain cotton yield and quality variation across planting dates under a double cropping system of cotton-wheat - Simeng Guo; Taijie Liu; Yingchun Han; Guoping Wang; Wenli Du; Fengqi Wu; Yabing Li; Lu Feng (Field Crops Research, 2023)

Application of Al-Fe Co-modified Rice-Straw Biochar to Fluoride Removal: Synthesis, Optimization, and Performance - Chaoshuo Hou; Wei Xiu; Huaming Guo; Simeng Li; Chunping Jiang (Water, Air, & Soil Pollution, 2023)

IFITM3 is a host restriction factor that inhibits porcine transmissible gastroenteritis virus infection - Kexin Yan; Simeng Feng; Jiahao Cheng; Fan Zheng; Zhiqiang Li; Zhibang Deng; Xiaomin Yuan (Veterinary Microbiology, 2023)

Comparative analysis of nitrate evolution patterns during pollution episodes: Method development and results from Tianjin, China - Yafei Li; Yan Han; Simeng Ma; Yufen Zhang; Haoqi Wang; Jingyi Yang; Lu Yao; Xiaohui Bi; Jianhui Wu; Yinchang Feng (Science of The Total Environment, 2023)

Green energy mismatch, industrial intelligence and economics growth: theory and empirical evidence from China - Yunwei Li; Qiuping Ji; Zijie Wang; Zishan Xiong; Simeng Zhan; Yiping Yang; Yu Hao (Environment, Development and Sustainability, 2022)

Heme oxygenase-1 protects against endotoxin-induced acute lung injury depends on NAD+-mediated mitonuclear communication through PGC1α/PPARγ signaling pathway - Simeng He; Jia Shi; Wenming Liu; Shihan Du; Yuan Zhang; Lirong Gong; Shuan Dong; Xiangyun Li; Qiaoying Gao; Jing Yang; Jianbo Yu (Inflammation Research, 2022)

TMEM92 acts as an immune-resistance and prognostic marker in pancreatic cancer from the perspective of predictive, preventive, and personalized medicine - Simeng Zhang; Xing Wan; Mengzhu Lv; Ce Li; Qiaoyun Chu; Guan Wang (EPMA Journal, 2022)

Heavy metals’ release characteristic of sewage sludge in alkaline treatment prior to anaerobic digestion - Jianlong Hu; Guanglong Wu; Xi Zheng; Simeng Li; Jixu Zhao; Cunzhen Liang (Water, Air, & Soil Pollution, 2022)

Correction to: Downregulation of fibronectin 1 attenuates ATRA‑induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2022)

Temporal trends and source apportionment of water pollution in Honghu Lake, China - Shuai Chen; Simeng Wang; Yanxi Yu; Mingjun Dong; Yanqiang Li (Environmental Science and Pollution Research, 2021)

Downregulation of fibronectin 1 attenuates ATRA-induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2021)

Phytoremediation of contaminants of emerging concern from soil with industrial hemp (Cannabis sativa L.): a review - Yudi Wu; Helen X. Trejo; Gang Chen; Simeng Li (Environment, Development and Sustainability, 2021)

Impact of Humic Acids on Phosphorus Retention and Transport - Yudi Wu; Simeng Li; Gang Chen (Journal of Soil Science and Plant Nutrition, 2020)

A comparison and case analysis between domestic and overseas industrial parks of China since the Belt and Road Initiative - Chao Ye; Simeng Li; Liang Zhuang; Xiaodan Zhu (Journal of Geographical Sciences, 2020)

Rainfall-induced reactivation mechanism of a landslide with multiple-soft layers - Yang Ren; Tianbin Li; Simeng Dong; Jieling Tang; Demin Xue (Landslides, 2020)

Contemporary strategies for enhancing nitrogen retention and mitigating nitrous oxide emission in agricultural soils: present and future - Simeng Li; Gang Chen (Environment, Development and Sustainability, 2020)

P53/PUMA are potential targets that mediate the protection of brain-derived neurotrophic factor (BDNF)/TrkB from etoposide-induced cell death in neuroblastoma (NB) - Zhongyan Hua; Yue Zhan; Simeng Zhang; Yudi Dong; Min Jiang; Fei Tan; Zhihui Liu; Carol J. Thiele; Zhijie Li (Apoptosis, 2018)

Cry1Ab Adsorption and Transport in Humic Acid-Coated Geological Formation of Alumino-Silica Clays - Hongying Yuan; Simeng Li; Junliang Liu; Chengyi Song; Gang Chen (Water, Air, & Soil Pollution, 2017)

Erratum to: The role of particle size of glyburide crystals in improving its oral absorption - Wenqian Yang; Yongjun Wang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

The role of particle size of glyburide crystals in improving its oral absorption - Yongjun Wang; Wenqian Yang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)